The effect of job satisfaction and family satisfaction on work- family conflict (W-FC) and family-work conflict (F-WC) among married female nurses in Shiraz-Iran - Namayandeh, Hajar; Juhari, Rumaya; Yaacob, Siti Nor (Canadian Center of Science and Education, 2011)
The present study highlights the significance of job satisfaction as one of the most important work factors on W-FC and F-WC. This paper also examines the effects of one of the essential family factor which is family satisfaction on W-FC and F-WC. The respondents for this study consist of 198 married female nurses working in public hospitals in Shiraz-Iran. The findings revealed that married female nurses with high level of job satisfaction tend to report low level of W-FC. Unlike previous studies, the finding also indicates that there is no significant relationship between the respondents’ job satisfaction and F-WC, which may be explained by the specific cultural context in Iran. This study also established that high level of family satisfaction is associated with low level of W-FC and F-WC. Implications are discussed and recommendations are made regarding future researches in this area.